Composite heat-insulating fireproof material with sandwich structure and preparation method of composite heat-insulating fireproof material
By using composite thermal insulation and fire-proof materials with sandwich structure in lithium-ion batteries, safety problems such as thermal runaway and fire catching of lithium-ion batteries are solved, and excellent thermal insulation and fire-proof performance and economy are achieved.
Patent Information
- Application Number
- CN202411697446.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-18
AI Technical Summary
During storage and use, lithium-ion batteries are prone to thermal runaway, ignition, or explosion due to chemical instability, causing safety hazards.
Composite thermal insulation and fire-resistant materials using sandwich structures include electronic-grade fiberglass fabric layer, ceramic silicone rubber layer and low-breathable polyurethane sponge layer. The fire-resistant and thermal insulation properties of the material are enhanced by the combined action of the ceramic layer of ceramic silicone rubber and the tensile strength of the fiberglass fabric.
It achieves excellent thermal insulation and fire resistance performance in high-temperature flame environments. The back temperature can be stably controlled below 50℃, and has low cost and high economicality. It is suitable for thermal insulation and fire resistance materials for lithium-ion batteries.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials and relates to a composite heat-insulating and fire-proof material with a sandwich structure and a preparation method thereof. Background Art
[0002] With the development of the new energy vehicle industry and the energy storage industry, the safety of power batteries and energy storage batteries has become an increasingly important focus of the industry. Due to the inherent chemical activity / instability of lithium-ion batteries, lithium-ion power / energy storage batteries are prone to thermal runaway or even fire / deflagration / explosion accidents during storage and operation due to bumps, punctures, shocks caused by external forces, or because of their inherent chemical instability. When a lithium-ion battery catches fire, the fire spreads extremely rapidly, and the firefighting time left for the energy storage power station is very short, and they can only wait for the fire to burn out; similarly, compared with the spontaneous combustion of fuel vehicles, when new energy vehicles equipped with lithium-ion power batteries spontaneously combust, the time left for passengers to escape is extremely short, which poses great danger to passengers. Therefore, with the development of the new energy vehicle industry and the energy storage industry, solving the resulting thermal runaway fire prevention problem has always been a key issue that needs to be solved.
[0003] In view of the excellent flame retardant and fireproof properties of silicone rubber, as well as its extremely low price and higher strength compared to aerogel materials (which have both excellent thermal insulation and fireproof properties, but extremely low strength and extremely high price), utilizing the excellent fireproof properties of silicone materials and giving them excellent thermal insulation properties to achieve excellent thermal insulation and fireproof properties while being economical is a very possible way to solve the thermal runaway fire prevention problem of lithium-ion batteries. Summary of the invention
[0004] In view of the above problems to be solved, the present invention proposes the following design ideas:
[0005] 1) On the basis of organic silicone rubber, ceramic flame retardant is added to form a ceramic layer through its ceramic properties when burned by high-temperature flames, thereby further enhancing the fire resistance and heat insulation properties of organic silicone rubber (i.e. ceramic silicone rubber);
[0006] 2) On the basis of ceramic silicone rubber, in order to prevent the ceramic layer from cracking due to slight expansion of the ceramic layer when the ceramic silicone rubber is burned by high-temperature flames to form a ceramic layer, thereby damaging the thermal insulation and fire resistance of the ceramic silicone rubber, glass fiber cloth is compounded on the ceramic silicone rubber. The glass fiber cloth with high tensile strength prevents the expansion and cracking of the ceramic layer, maintains the excellent thermal insulation and fire resistance of the ceramic silicone rubber, and at the same time uses the inherent fire resistance of the glass fiber cloth to further enhance the fire resistance of the ceramic silicone rubber;
[0007] 3) On the basis of the above, in order to further enhance the thermal insulation performance, a sandwich structure is designed, which includes, from top to bottom, an electronic-grade glass fiber cloth layer, a ceramic silicone rubber layer, a low-permeability polyurethane sponge layer (high closed-pore rate), a ceramic silicone rubber layer, and an electronic-grade glass fiber cloth layer; the high closed-pore rate of the low-permeability polyurethane sponge is utilized to further reduce the circulation and diffusion of heat, thereby enhancing the thermal insulation performance of the final thermal insulation and fireproofing material. At the same time, utilizing the few open-cell bubbles of the low-permeability polyurethane sponge, the ceramic silicone rubber compound is pressed into the open-cell bubbles during calendering with a double-roll calender. After curing, the bonding force between the low-permeability polyurethane sponge layer and the upper and lower ceramic silicone rubber layers (silicone materials have extremely low surface energy and very low bonding force with general materials) is strengthened, and at the same time, the open-cell bubbles of the polyurethane sponge layer are sealed, thereby enhancing the thermal insulation performance of the final thermal insulation and fireproofing material;
[0008] The sandwich structure composite heat-insulating and fire-proofing material prepared by the present invention is very suitable for use as a heat-insulating and fire-proofing material for lithium-ion batteries, thereby solving the safety problems caused by battery thermal runaway and fire in the new energy automobile industry and the energy storage industry.
[0009] An object of the present invention is to provide a sandwich structure composite heat insulation and fireproof material having the following characteristics:
[0010] 1) It has excellent heat insulation and fireproof performance. When one side is continuously sprayed and burned by a butane spray gun for 5 minutes, the temperature of the back side can be stably controlled below 50°C, and there is no flame or spark after the butane spray gun is removed or turned off;
[0011] 2) Compared with aerogel materials with similar thermal insulation and fireproof properties, it has lower cost and higher economy.
[0012] Another object of the present invention is to provide a method for preparing a sandwich structure composite heat-insulating and fire-proofing material.
[0013] According to one embodiment of the present invention, a sandwich structure composite heat-insulating fireproof material is provided, and the heat-insulating fireproof material includes five layers, which are, from top to bottom, an electronic-grade glass fiber cloth layer, a ceramic silicone rubber layer, a polyurethane sponge layer, a ceramic silicone rubber layer, and an electronic-grade glass fiber cloth layer. Among them, the thickness of the electronic-grade glass fiber cloth is 0.1-0.2 mm; the thickness of the ceramic silicone rubber layer is 0.3-1 mm; the polyurethane sponge layer is a polyester sponge or a polyether sponge, with a thickness of 1-10 mm. The sandwich structure composite heat-insulating fireproof material has both excellent heat-insulating and fire-proof properties, as well as extremely low prices and higher strength compared to aerogel materials. It is very suitable for use as a heat-insulating fireproof material for lithium-ion batteries, thereby solving the safety problems caused by thermal runaway and fire in the new energy vehicle industry and the energy storage industry; it is also very suitable for scenes with strict requirements for heat insulation, heat preservation and fire prevention, such as building exterior walls.
[0014] In one embodiment, in the sandwich structure composite heat insulation and fireproof material, the density of the electronic grade glass fiber cloth is 204kg / m 3 , warp tensile strength ≥400N / 25mm, weft tensile strength ≥300N / 25mm;
[0015] In one embodiment, in the sandwich structure composite heat insulation and fireproof material, the polyurethane sponge is a flame retardant sponge or a non-flame retardant sponge with a high closed porosity, and the air permeability is 30 L / m 2 / s~150L / m 2 / s;
[0016] In one embodiment, in the sandwich structure composite heat insulation and fireproof material, the ceramic silicone rubber includes two components A and B, and the mixing ratio of component A to component B is 1:1; component A includes vinyl polysiloxane, base glue, crosslinking agent, catalyst, inhibitor, and flame retardant; component B includes vinyl polysiloxane, base glue, crosslinking agent, and flame retardant;
[0017] In one embodiment, in the A and B components of the ceramic silicone rubber, the vinyl polysiloxane includes one or more of a double-terminal vinyl polysiloxane, a double-terminal side-chain vinyl polysiloxane, and a double-terminal methyl side-chain vinyl polysiloxane, preferably a double-terminal vinyl polysiloxane; in the A and B components, the crosslinking agent includes one or more of a polysiloxane containing a silicon hydrogen group in the side chain and a polysiloxane containing a silicon hydrogen group in the double terminal, preferably a polysiloxane containing a silicon hydrogen group in the side chain;
[0018] In one embodiment, in the A and B components of the ceramic silicone rubber, the viscosity of the vinyl polysiloxane is 10000mPa·S / 25°C to 65000mPa·S / 25°C; the silane content of the crosslinking agent (silane-containing polysiloxane) is 16mmol / g; the base rubber is a commercially available product with a viscosity of 750000mPa·S / 25°C to 1200000mPa·S / 25°C;
[0019] In one embodiment, in component A of the ceramic silicone rubber, the catalyst is one or more of a simple substance, an inorganic compound, and an organic complex of a Group VIII metal; preferably, the catalyst is one or more of a simple substance, an inorganic compound, and an organic complex of metal platinum; more preferably, the catalyst is an organic complex of metal platinum; most preferably, the catalyst is platinum (0)-1,3-diethene-1,1,3,3-tetramethyldisiloxane, i.e., Custer's reagent; and the inhibitor is an alkynyl alcohol.
[0020] In one embodiment, in the A component of the ceramic silicone rubber, the addition ratio of vinyl polysiloxane and base glue is 3:7 to 7:3; the addition ratio of the flame retardant to the sum of the vinyl polysiloxane and the base glue is 1:1 to 1.5:1; the addition ratio of the crosslinking agent to the sum of the vinyl polysiloxane and the base glue is 0.0036:1 to 0.0054:1; the addition ratio of the catalyst and the inhibitor to the sum of the vinyl polysiloxane and the base glue is 0.005:1; in the B component of the ceramic silicone rubber, the addition ratio of vinyl polysiloxane and the base glue is 3:7 to 7:3; the addition ratio of the flame retardant to the sum of the vinyl polysiloxane and the base glue is 1:1 to 1.5:1; the addition ratio of the crosslinking agent to the sum of the vinyl polysiloxane and the base glue is 0.0036:1 to 0.0054:1;
[0021] In one embodiment, in the A and B components of the ceramic silicone rubber, the flame retardant is a composite flame retardant that can be ceramicized at high temperature;
[0022] According to another aspect of the present invention, there is provided a method for preparing a sandwich structure composite heat-insulating and fire-proofing material, comprising the following steps:
[0023] 1) Preparation of ceramic silicone rubber compound
[0024] The A and B components are mixed in proportion and stirred with a double planetary mixer at a twist pulp speed of 100RPM and a double-layer dispersion disk speed of 3000RPM respectively, and vacuumed to -100KPa while stirring, and cooled by a circulating water cooler simultaneously, and the material temperature of the A and B components is controlled below 20°C, and stirred for 20 minutes to obtain the A and B components of the ceramic silicone rubber compound;
[0025] 2) Preparation of sandwich structure composite thermal insulation and fireproof materials
[0026] The A and B components of the ceramic silicone rubber compound are mixed at a speed of 4000RPM through the feeding system and injected onto the electronic grade glass fiber cloth, the polyurethane sponge is spread on the ceramic silicone rubber compound, flattened by a double-roll calender, and placed in a blast drying oven for heating and curing at 110-130°C for 5 minutes, to obtain semi-finished products of polyurethane sponge, ceramic silicone rubber, and electronic grade glass fiber cloth from top to bottom. The semi-finished product is taken out and cooled to room temperature, and then the A and B components of the ceramic silicone rubber compound are mixed again at a speed of 4000RPM through the feeding system and injected onto the semi-finished polyurethane sponge, the electronic grade glass fiber cloth is spread on the ceramic silicone rubber compound, flattened by a double-roll calender, and placed in a blast drying oven for heating and curing at 110-130°C for 5 minutes to obtain a finished sandwich structure composite heat insulation and fireproof material.
[0027] The sandwich structure composite thermal insulation and fireproofing material prepared by the preparation method provided by the present invention has excellent thermal insulation and fireproofing properties, as well as extremely low price and higher strength compared to aerogel materials. It is very suitable for use as a thermal insulation and fireproofing material for lithium-ion batteries, thereby solving the safety problems caused by thermal runaway and fire of batteries in the new energy vehicle industry and the energy storage industry; it is also very suitable for scenes with strict requirements on thermal insulation and fireproofing, such as building exterior walls. DETAILED DESCRIPTION
[0028] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.
[0029] All basic raw materials used in the following examples are commercially available products.
[0030] Example 1
[0031] The preparation of sandwich structure composite heat insulation and fireproof material includes the following steps:
[0032] 1) Preparation of ceramic silicone rubber compound
[0033] The vinyl polysiloxane with a viscosity of 10000mPa·S / 25℃ (VS10000 produced by Anbiya Special Silicone (Nantong) Co., Ltd.) and the base glue with a viscosity of 750000mPa·S / 25℃ (6345 base glue produced by Dongguan Chuanshi Electronic Technology Co., Ltd.) in component A were weighed in a ratio of 3:7. The flame retardant (CFR-2 flame retardant produced by Anhui Yishitong Material Technology Co., Ltd.) was weighed in a ratio of 1.2:1 to the sum of the flame retardant and the vinyl polysiloxane and the base glue. Flammable agent), a cross-linking agent with a hydrogen content of 16 mmol / g (side chain hydrogen-containing silicone oil H=1.6 from Jiande Polymer New Materials Co., Ltd.) was weighed according to the addition ratio of the cross-linking agent to the sum of vinyl polysiloxane and base gum of 0.0054:1, and a catalyst (PT-5000 from Zhongshan Zijun Chemical) and an inhibitor (OS121 from Shenzhen Ousbang New Materials Co., Ltd.) were weighed according to the addition ratio of the catalyst and the inhibitor to the sum of vinyl polysiloxane and base gum of 0.005:1. The vinyl polysiloxane with a viscosity of 10000mPa·S / 25℃ (VS10000 from Anbia Special Silicone (Nantong) Co., Ltd.) and the base glue with a viscosity of 750000mPa·S / 25℃ (6345 base glue from Dongguan Chuanshi Electronic Technology Co., Ltd.) in component B were weighed in a ratio of 3:7, the flame retardant (CFR-2 flame retardant from Anhui Yishitong Materials Technology Co., Ltd.) was weighed in a ratio of 1.2:1 between the flame retardant and the sum of the vinyl polysiloxane and the base glue, and the cross-linking agent with a hydrogen content of 16mmol / g (side chain hydrogenated silicone oil H=1.6 from Jiande City Polymer New Materials Co., Ltd.) was weighed in a ratio of 0.0054:1 between the cross-linking agent and the sum of the vinyl polysiloxane and the base glue. Then, the A and B components were stirred respectively by a double planetary mixer at a twist pulp speed of 100RPM and a double-layer dispersion disk speed of 3000RPM, and vacuumed to -100KPa while stirring. The mixture was cooled by a circulating water cooler simultaneously, and the material temperature of the A and B components was controlled to be below 20°C. The mixture was stirred for 20 minutes to obtain the A and B components of the ceramic silicone rubber compound.
[0034] 2) Preparation of sandwich structure composite thermal insulation and fireproof materials
[0035] The prepared ceramic silicone rubber compound A and B components are mixed at a speed of 4000RPM through a feeding system and injected onto a 0.2mm 7628 electronic grade glass fiber cloth. The 4.4mm thick KZ314FM-70PPI polyurethane sponge produced by our company is spread on the ceramic silicone rubber compound, and is flattened by a double-roll calender according to a ceramic silicone rubber layer thickness of 0.6mm. The mixture is placed in a blast drying oven and heated and cured at 110-130°C for 5 minutes to obtain semi-finished products comprising polyurethane sponge, ceramic silicone rubber, and electronic grade glass fiber cloth from top to bottom. The semi-finished product was taken out and cooled to room temperature, and then the A and B components of the ceramic silicone rubber compound were mixed again at a speed of 4000RPM through the feeding system and injected onto the smooth surface of the polyurethane sponge of the semi-finished product, and 0.2mm 7628 electronic grade glass fiber cloth was spread on the ceramic silicone rubber compound, and the ceramic silicone rubber layer was flattened by a double-roll calender according to a thickness of 0.6mm. The material was placed in a blast drying oven and heated and cured at 110-130°C for 5 minutes to obtain a 5mm thick finished sandwich structure composite thermal insulation and fireproof material.
[0036] Example 2
[0037] The difference between Example 2 and Example 1 is that in step 1) of preparing the ceramic silicone rubber adhesive, in components A and B, the ratio of vinyl polysiloxane to base rubber is 7:3, and the rest is consistent with Example 1.
[0038] Example 3
[0039] The difference between Example 3 and Example 1 is that in step 1) of preparing the ceramic silicone rubber compound, the viscosity of the vinyl polysiloxane used in components A and B is 65000 mPa·S / 25°C (VS65000 from Ambiah Special Silicone (Nantong) Co., Ltd.), and the rest is consistent with Example 1.
[0040] Example 4
[0041] The difference between Example 4 and Example 1 is that, in step 1) in the preparation of the ceramic silicone rubber adhesive, the viscosity of the vinyl polysiloxane used in components A and B is 65000 mPa·S / 25°C (VS65000 of Ambia Special Silicone (Nantong) Co., Ltd.), and the ratio of vinyl polysiloxane to base rubber is 7:3, and the rest is consistent with Example 1.
[0042] Comparative Example 1
[0043] Comparative Example 1 is a type IV aerogel felt (a composite product of nano aerogel and inorganic fiber) purchased from Guangdong Alison High-tech Technology Co., Ltd.
[0044] Comparative Example 2
[0045] Comparative Example 2 uses the same ceramic silicone rubber compound as Example 1, which is mixed and injected onto 0.2 mm 7628 electronic grade glass fiber cloth through the same feeding system at the same rotation speed of 4000 RPM, and then the 0.2 mm 7628 electronic grade glass fiber cloth is spread flat on the ceramic silicone rubber compound, and is flattened by a double-roll calender according to a ceramic silicone rubber layer thickness of 5.6 mm. It is placed in a blast drying oven and heated and cured at 110-130°C for 5 minutes to obtain a finished sandwich structure composite thermal insulation and fireproof material with a thickness of 6 mm.
[0046] The physical property test results of the heat-insulating and fire-proof materials prepared in Examples 1 to 4 and Comparative Examples 1 and 2 are shown in Table 1.
[0047]
[0048] It can be seen from Table 1 that compared with the aerogel felt of Comparative Example 1, on the basis of substantially the same density and thickness, the sandwich structure composite heat-insulating fireproof materials of Examples 1 to 4 prepared according to the design concept of the present invention have a slightly higher thermal conductivity, but the difference is not large. And the sandwich structure composite heat-insulating fireproof materials prepared in Examples 1 to 4, like the aerogel felt of Comparative Example 1, have a fireproof grade of Class A (non-combustible grade). The sandwich structure composite heat-insulating fireproof materials prepared in Examples 1 to 4 and one surface of the aerogel felt of Comparative Example 1 were continuously and uninterruptedly sprayed and burned by a butane spray gun (flame temperature is about 1300°C). For up to 5 minutes, the temperature of the other surface of the aerogel felt of Comparative Example 1 was always maintained at about room temperature, while the temperature of the other surface of the sandwich structure composite heat-insulating fireproof materials prepared in Examples 1 to 4 was always below 50°C.
[0049] Compared with the solid sandwich structure ceramic silicone rubber of the same thickness in comparative example 2, the sandwich structure composite heat insulation and fireproof materials of Examples 1 to 4 prepared according to the design concept of the present invention have a density several times lower and a thermal conductivity coefficient nearly one order of magnitude lower. Although the flame retardant level is the same, the back temperature of comparative example 2 is as high as 385°C when a butane spray gun is used to continuously spray and burn one surface for 5 minutes, while the back temperature of the sandwich structure composite heat insulation and fireproof materials prepared by Examples 1 to 4 of the present invention is always below 50°C, and the heat insulation effect is significant. As time goes by, although the back temperature of the sandwich structure composite heat insulation and fireproof materials will continue to rise under the continuous burning of the butane spray gun; but its excellent heat insulation and fireproof performance can still effectively suppress the thermal runaway of lithium-ion power batteries and energy storage batteries within a certain period of time, which is convenient for maintenance by engineering and technical personnel; in the event of a fire, it can also give passengers on new energy vehicles and staff in energy storage power stations sufficient reaction and escape time. That is to say, although Comparative Example 2 can effectively prevent flames due to the absence of a sponge interlayer, its heat insulation effect is not as good as that of Examples 1-4, especially before the sponge melts, heat conduction penetrates the multi-layer composite material slowly, and the heated surface and the heat conducting surface can maintain a high temperature difference within a few minutes, thereby gaining a stable and longer time window for the implementation of other intervention measures such as cooling and temperature control.
[0050] In summary, the fireproof performance of the sandwich structure composite thermal insulation and fireproof material prepared by the present invention is comparable to that of aerogel felt. Although the thermal conductivity is slightly higher than that of aerogel felt, it is much lower than that of solid ceramic silicone rubber of the same thickness; the thermal insulation performance when resistant to high-temperature flame burning is slightly worse than that of aerogel felt, but it is also roughly similar, and much stronger than that of ceramic silicone rubber of the same thickness. Due to the cost of raw materials and the cost of the preparation process, the cost of aerogel felt in Comparative Example 1 is relatively high, and its cost is many times higher than that of the sandwich structure composite thermal insulation and fireproof material prepared by Examples 1 to 4 of the present invention. Therefore, the sandwich structure composite thermal insulation and fireproof material provided by the present invention has lower cost and higher economy than aerogel materials with similar thermal insulation and fireproof properties on the basis of having both excellent thermal insulation and fireproof properties.
[0051] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.
Claims
1. A sandwich structure composite heat insulation and fireproof material, characterized in that: The heat-insulating fireproof material comprises five layers, which are, from top to bottom, an electronic-grade glass fiber cloth layer, a ceramic silicone rubber layer, a polyurethane sponge layer, a ceramic silicone rubber layer, and an electronic-grade glass fiber cloth layer. The thickness of the electronic-grade glass fiber cloth is 0.1 to 0.2 mm; the thickness of the ceramic silicone rubber layer is 0.3 to 1 mm; the polyurethane sponge layer is a polyester sponge or a polyether sponge with a thickness between 1 and 10 mm; The viscosity of vinyl polysiloxane is 10000mPa·S / 25℃~65000mPa·S / 25℃; the silane hydrogen content of the crosslinking agent is 16mmol / g; the viscosity of the base rubber is 750000mPa·S / 25℃~1200000mPa·S / 25℃; the ceramic silicone rubber includes two components A and B, and the mixing ratio of component A to component B is 1:1; component A includes vinyl polysiloxane, base rubber, crosslinking agent, catalyst, inhibitor, and flame retardant; component B includes vinyl polysiloxane, base rubber, crosslinking agent, and flame retardant; in component A, the addition ratio of vinyl polysiloxane and base rubber is 3:7~7:3; The addition ratio of the flame retardant to the sum of the vinyl polysiloxane and the base glue is 1:1 to 1.5:1; the addition ratio of the crosslinking agent to the sum of the vinyl polysiloxane and the base glue is 0.0036:1 to 0.0054:1; the addition ratio of the catalyst and the inhibitor to the sum of the vinyl polysiloxane and the base glue is 0.005:1; in component B, the addition ratio of vinyl polysiloxane and the base glue is 3:7 to 7:3; the addition ratio of the flame retardant to the sum of the vinyl polysiloxane and the base glue is 1:1 to 1.5:1; the addition ratio of the crosslinking agent to the sum of the vinyl polysiloxane and the base glue is 0.0036:1 to 0.0054:
1.
2. The sandwich structure composite heat insulation and fireproof material according to claim 1, characterized in that: The density of electronic grade glass fiber cloth is 204kg / m 3 , the tensile strength in the warp direction is ≥400N / 25mm, and the tensile strength in the weft direction is ≥300N / 25mm.
3. The sandwich structure composite heat insulation and fireproof material according to claim 1, characterized in that: The polyurethane sponge is a flame retardant sponge or non-flame retardant sponge with a high closed-pore rate and an air permeability of 30L / m 2 / s~150L / m 2 / s.
4. According to claim 1, a sandwich structure composite heat insulation and fireproof material, characterized in that: The vinyl polysiloxane is a mixture of one or more of dual-terminal vinyl polysiloxane, dual-terminal side-chain vinyl polysiloxane and dual-terminal methyl side-chain vinyl polysiloxane.
5. The sandwich structure composite heat insulation and fireproof material according to claim 4, characterized in that: The vinyl polysiloxane is a double-terminated vinyl polysiloxane.
6. The sandwich structure composite heat insulation and fireproof material according to claim 1, characterized in that: The crosslinking agent is a mixture of one or more of polysiloxane containing silane hydrogen groups on the side chains and polysiloxane containing silane hydrogen groups at both ends.
7. The sandwich structure composite heat insulation and fireproof material according to claim 6, characterized in that: The crosslinking agent is a polysiloxane containing a silicon hydrogen group in the side chain.
8. The sandwich structure composite heat insulation and fireproof material according to claim 1, characterized in that: The catalyst is a mixture of one or more of a simple substance, an inorganic compound and an organic complex of a Group VIII metal.
9. The sandwich structure composite heat insulation and fireproof material according to claim 8, characterized in that: The catalyst is platinum (0)-1,3-diethene-1,1,3,3-tetramethyldisiloxane, and the inhibitor is alkynyl alcohol.
10. A method for preparing a composite heat-insulating and fire-proof material having a sandwich structure as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: 1) Preparation of ceramic silicone rubber compound The A and B components are mixed in proportion and stirred with a double planetary mixer at a twist pulp speed of 100RPM and a double-layer dispersion disk speed of 3000RPM respectively, and vacuumed to -100KPa while stirring, and cooled by a circulating water cooler simultaneously, and the material temperature of the A and B components is controlled below 20°C, and stirred for 20 minutes to obtain the A and B components of the ceramic silicone rubber compound; 2) Preparation of sandwich structure composite thermal insulation and fireproof materials The prepared and mixed ceramic silicone rubber compound A and B components are mixed at a speed of 4000RPM through a feeding system and injected onto an electronic-grade glass fiber cloth, a polyurethane sponge is spread on the ceramic silicone rubber compound, flattened by a double-roll calender, and placed in a blast drying oven for heating and curing at 110-130°C for 5 minutes to obtain semi-finished products which are polyurethane sponge, ceramic silicone rubber, and electronic-grade glass fiber cloth from top to bottom; the semi-finished product is taken out and cooled to room temperature, and then the A and B components of the ceramic silicone rubber compound are mixed again at a speed of 4000RPM through a feeding system and injected onto the semi-finished polyurethane sponge, the electronic-grade glass fiber cloth is spread on the ceramic silicone rubber compound, flattened by a double-roll calender, and placed in a blast drying oven for heating and curing at 110-130°C for 5 minutes to obtain a finished sandwich structure composite thermal insulation and fireproof material.